2019
DOI: 10.1016/j.cegh.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antimicrobial therapy and patient adherence in diabetic foot infections

Abstract: Background/objectives: Diabetic foot infections (DFI) are common complications among diabetics. These wounds can cause discomfort and often become infected. In India, currently there is a paucity of data on patient adherence towards antibiotic use in DFIs. Therefore, this study was aimed to evaluate antimicrobial susceptibility pattern, antimicrobial therapy and its adherence in DFI patients. Method: A prospective observation study (N = 150, newly diagnosed DFI patients) was conducted in Kasturba hospital, Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The analysis was conducted independently by all team members (ZX, ML, ECAL, GLJ, DL, and BB) following the guidelines set out by Smith, Flowers, and Larkin. 19 Upon the initial reading of the first three transcripts, there was an annotating phase of analysis. Descriptive, linguistic, and conceptual comments were noted, followed by identifying emergent themes within the text.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was conducted independently by all team members (ZX, ML, ECAL, GLJ, DL, and BB) following the guidelines set out by Smith, Flowers, and Larkin. 19 Upon the initial reading of the first three transcripts, there was an annotating phase of analysis. Descriptive, linguistic, and conceptual comments were noted, followed by identifying emergent themes within the text.…”
Section: Methodsmentioning
confidence: 99%
“…[13][14][15] However, despite provision of appropriate information and guidance, patients' self-care is often suboptimal, and adherence to foot self-care recommendations and compliance to medication remains low. [16][17][18][19] In addition, although early detection and referral of patients is crucial, [20][21][22] there are still a number of patients who delay reporting foot symptoms to health professionals, and up to 40% to 60% of amputations are related to patient delay. 23 Singapore has the highest rate of DLEA in the world, 24 and the trend is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…[ 30 , 31 , 68 , 69 ] The possible occurrence of low DFU patients could be due to under-reporting, the lack of awareness, younger age or as shorter duration of diabetes. [ 58 , 70 ] Microbiological studies of DFU were reported from urban cities, irrespective of the prevalence of individuals with diabetes patients in those regions. [ 1 ] In India, diabetes is more prevalent in urban areas of the states of Tripura, Chandigarh, Tamil Nadu, Jharkhand and Andhra Pradesh.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, male patients were predominantly reported with a bacterial infection in DFU (71.59% males and 28.39% females; SE = 1.41; n = 43). The highest proportion of male patients was reported to be 92.6%,[ 58 ] and the lowest proportion of male patients was reported at 54%. [ 59 ] The average age of the patients with DFU in India is 56.39 ( n = 23 studies).…”
Section: Ethodsmentioning
confidence: 99%
“…A study undertaken in India found that the prescribing patterns of empirical antibiotic regimens did not comply with the antibiotic policy of the study hospital. [57] In contrast, an Australian study determined that 83% of patients received empirical antibiotic treatment that complied with national guidelines. [58] A study carried out in Poland yielding outcomes similar to our findings found that although there was good adherence to local prescribing guidelines, the guidelines themselves did not cover the most common pathogens responsible for DFU infection.…”
Section: Researchmentioning
confidence: 99%